Health Literacy of Pain Management in Older Patients with Cancer - Prasertsri, Nusara; Leaungsomnapa, Yosapon; Wamalun, Chaliya; Taptimhin, Sopit; Ngamkham, Srisuda; Sirisupaluk, Piriyaluk; Tiyapan, Wilailuk; Chareannukul, Apiradee (Nursing Journal of The Ministry of Public Health, 2023)
Health literacy affects health status and health outcomes. Cancer pain is a major problem in older patients with cancer. This cross-sectional descriptive research study aimed to investigate health literacy, pain intensity, pain perception and pain management in older patients with cancer. The sample consisted of 880 older patients with cancer who were registered as patients of 4 hospitals. The sample was selected purposively according to the characteristics of inclusion criteria. The research instruments consisted of a health literacy questionnaire for pain management, and a Thai version of the Brief Pain Inventory (BPI) pain questionnaire. The content validity index of the research instrument was tested that was .91 to 1.0. Reliability was tested using Cronbach's alpha coefficient, which gave a value of .81. Data were analyzed using descriptive statistics. The results found that older patients with cancer had overall health literacy regarding pain management at a poor to fair level. The patients had moderate pain. Pain had the greatest effect on sleep. Pain management was mainly through medication. The results of pain management were good. In 5.1%of patients, pain management was insufficient. The results of this study provide essential information for health personnel when planning to promote health literacy and pain management in older patients with cancer.